Safe Space for Women Survivors: Activities of the Kawan Puan Banyuwangi Community in Building Mental Health - Setyaningsih, Wahyu; Waryunah Irmawati; Diana Trisnawati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The persistent patriarchal culture in Indonesian society does not allow all women to get a safe space, especially women survivors. The purpose of this study is to explain the patriarchal culture in Banyuwangi Regency and the history of the Kawan Puan Banyuwangi Community, as well as analyze their activities in building mental health, so that women survivors can have safe spaces. This research’s novelty lies in examining the activities of the Kawan Puan Banyuwangi Community in creating safe spaces through the mental development of women survivors. So the questions of this research include what the patriarchal culture is in Banyuwangi Regency, what is the history of the birth of the Kawan Puan Banyuwangi Community, and how are the activities of the Kawan Puan Banyuwangi Community in building mental health, so that women survivors get a safe space? This research method used a case study with a historical approach in the Kawan Puan Banyuwangi Community. The analysis used Abraham Maslow's Hierarchy of Needs Theory. The results of the study indicate the existence of a patriarchal culture in Banyuwangi Regency in 2021, including 38% of cases of sexual intercourse, 12 % of obscenity, 23% of psychological violence, 19% of sexual violence, 4% of physical violence, and 4% of neglect, resulting in women lacking access to safe spaces. The Kawan Puan Banyuwangi Community builds the mental health of women survivors through sharing activities without judgment, providing psychological assistance for survivors to map their problems appropriately, and creating a women-support-women habituation, which is key to safe spaces. Therefore, safe spaces need to be built collectively by various parties; all parties must have knowledge of how to protect women.